Dinamika Pembelajaran Bahasa Arab di Indonesia: Dynamics of Arabic Language Learning in Indonesia - Imam Bonjol Jauhari (Fenomena, 2017)
The weak mastery of Arabic among graduates of Islamic educational institutions in Indonesia remains a common complaint, indicating ineffective teaching and learning processes despite Arabic receiving a significant portion of the curriculum. This article discusses the dynamics of Arabic language learning in Indonesia by tracing the historical development of its instruction, from verticalistic methods to communicative approaches. The purpose of this paper is to identify the factors that dynamize the Arabic teaching and learning process. Through literature review and analysis of curriculum policies from various periods, it was found that six models of Arabic language teaching have developed, with aural-oral and communicative approaches being the latest. Key findings indicate that learning success heavily depends on three main components: professional teachers who master both language and methodology, highly motivated students, and supporting facilities such as libraries, language laboratories, textbooks, teaching aids, language environment (bi'ah), and Arabic language activities. It is concluded that dynamizing Arabic language learning requires the simultaneous integration of these three components, and it is recommended to strengthen professional teacher organizations and create a conducive language environment in educational institutions. Lemahnya penguasaan bahasa Arab oleh lulusan lembaga pendidikan Islam di Indonesia masih menjadi keluhan umum, menunjukkan proses belajar mengajar yang belum efektif meskipun bahasa Arab mendapat porsi besar dalam kurikulum. Artikel ini membahas dinamika pembelajaran bahasa Arab di Indonesia dengan menelusuri perkembangan historis pengajarannya, mulai dari metode vertikalistis hingga pendekatan komunikatif. Tujuan penulisan adalah untuk mengidentifikasi faktor-faktor yang mendinamisasi proses belajar mengajar bahasa Arab. Melalui kajian literatur dan analisis kebijakan kurikulum dari berbagai periode, ditemukan bahwa enam model pengajaran bahasa Arab telah berkembang, dengan pendekatan aural-oral dan komunikatif menjadi yang terbaru. Temuan penting menunjukkan bahwa keberhasilan pembelajaran sangat bergantung pada tiga komponen utama: guru profesional yang menguasai bahasa dan metodologi, siswa dengan motivasi tinggi, serta sarana penunjang seperti perpustakaan, laboratorium bahasa, buku teks, alat bantu, lingkungan bahasa (bi'ah), dan aktivitas kebahasaaraban. Disimpulkan bahwa dinamisasi pembelajaran bahasa Arab memerlukan integrasi ketiga komponen tersebut secara simultan, dan direkomendasikan penguatan organisasi profesi guru serta penciptaan lingkungan bahasa yang kondusif di lembaga pendidikan.